Whispering tales: using augmented reality to enhance cultural landscapes and Indigenous values. (September 2019) - Marques, Bruno; McIntosh, Jacqueline; Carson, Hannah
Increasingly, our built and natural environments are becoming hybrids of real and digital entities where objects, buildings and landscapes are linked online in websites, blogs and texts. In the case of Aotearoa New Zealand, modern lifestyles have put Māori Indigenous oral narratives at risk of being lost in a world dominated by text and digital elements. Intangible values, transmitted orally from generation to generation, provide a sense of identity and community to Indigenous Māori as they relate and experience the land based on cultural, spiritual, emotion, physical and social values. Retaining the storytelling environment through the use of augmented reality, this article extends the biophysical attributes of landscape through embedded imagery and auditory information. By engaging with Ngāti Kahungunu ki Wairarapa, a design approach has been developed to illustrate narratives through different media, in a way that encourages a deeper and broader bicultural engagement with landscape.